Late Quaternary environments of central Mexico : a diatom record - Metcalfe, S (1986)
The nature and extent of environmental change over the Late Quaternary in Central Mexico is still uncertain. This study addresses the problem through an investigation of subfossil diatom assemblages in lacustrine sediments. As some doubt has been cast upon the reality of climatic change in Mexico, the variations in climate experienced over the archaeological and historical periods are described and possible explanations put forward in terms of the mechanisms of the present-day climate. The choice of technique and background to the region of the Neovolcanic Axis (Central Mexico) are outlined. As little is known of the modern aquatic environment of Central Mexico, a limnological survey was undertaken. The results of the analyses are discussed and possible trends of chemical evolution described. The modern diatom flora is presented for three areas and the results analysed using multivariate statistical techniques (TWINSPAN and DECORANA). These techniques highlight the importance of habitat in determining diatom assemblages. Subfossil diatom sequences are described from the Zacapu Basin, Michoacán (covering the last 28,000 years) and from the Upper Lerma Basin, Estado de México (covering about the last 11,600 years). Additional palaeoenvironmental information is provided by analyses of inorganic and organic geochemistry. In Central Mexico, wetter conditions probably prevailed prior to 25,000 (possibly 28,000) yr BP. In the Holocene, a dry event occurred between 7,500 and 7,000 yr BP, followed by a (?) major transgression soon afterwards. The period 4,500 - 4,000 yr BP appears to have been very dry, becoming wetter in the period 3,000 to 2,000 yr BP. Conditions were dry again by 1,300 yr BP. Man appears to have been an important agent of environmental change in Central Mexico over the last 3,000 years. His influence, extending into the Post-Hispanic period, is recorded in both the study areas. The results from the Zacapu and Upper Lerma basins fit well into the chronology of climatic change being developed for Central and northern South America.